Tantangan dan Peluang Gereja Dalam Pembentukan Karakter di Era Modern - Lumbantobing, Kristin Danayun; Siagian, Riris Johanna (EDULEAD: Journal of Christian Education and Leadership, 2025)
This study analyzes the implementation of contemporary theology in the formation of Christian character within the context of the modern era, marked by rapid social change, digitalization, and globalization. Employing a qualitative approach with a descriptive-analytical method, this research is based on an extensive literature review of contemporary theological writings, church documents, and scholarly works related to Christian character formation, discipleship, and church leadership. The study examines how contemporary theology functions as a contextual framework that bridges enduring biblical doctrines with present-day cultural, technological, and ethical challenges. The findings indicate that contemporary theology plays a crucial role in shaping Christian character by encouraging contextualized worship practices, integrative faith education, and holistic discipleship models that emphasize spiritual, moral, social, and intellectual dimensions. Furthermore, effective character formation is closely linked to discipleship approaches grounded in relational community, mentoring, and spiritual disciplines, as well as leadership models characterized by servant leadership, collaboration, and ethical integrity. In response to digitalization and globalization, the church is also called to develop strategies that integrate digital literacy, ethical discernment, and social engagement as essential components of faith formation. This study concludes that the formation of Christian character in the modern era requires a balanced integration of contemporary theological reflection, contextual discipleship, adaptive church leadership, and responsible engagement with digital culture. Such an integrative approach enables the church to remain faithful to biblical foundations while responding constructively to the complexities of modern life, ensuring that Christian faith is lived authentically as a transformative way of life rather than merely a doctrinal system.AbstrakPenelitian ini menganalisis implementasi teologi kontemporer dalam pembentukan karakter Kristen di era modern yang ditandai oleh perubahan sosial, digitalisasi, dan globalisasi yang pesat. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis melalui studi kepustakaan terhadap literatur teologi kontemporer, dokumen gereja, serta kajian ilmiah yang membahas pembentukan karakter Kristen, pemuridan, dan kepemimpinan gereja. Kajian ini menempatkan teologi kontemporer sebagai kerangka reflektif yang menjembatani ajaran Alkitab yang bersifat normatif dengan tantangan budaya, teknologi, dan etika masa kini. Hasil penelitian menunjukkan bahwa teologi kontemporer berperan penting dalam pembentukan karakter Kristen melalui praktik ibadah yang dikontekstualisasikan, pendidikan iman yang integratif, serta model pemuridan holistik yang mencakup dimensi spiritual, moral, sosial, dan intelektual. Pembentukan karakter yang efektif juga sangat bergantung pada model pemuridan berbasis relasi, mentoring, dan disiplin rohani, serta kepemimpinan gereja yang meneladani kepemimpinan Kristus yang melayani, kolaboratif, dan berintegritas. Dalam menghadapi tantangan globalisasi dan media digital, gereja perlu mengembangkan strategi pembinaan yang mengintegrasikan literasi digital, ketajaman etis, dan pelayanan sosial sebagai bagian dari proses formasi iman. Penelitian ini menyimpulkan bahwa pembentukan karakter Kristen di era modern menuntut integrasi yang seimbang antara refleksi teologi kontemporer, pemuridan yang kontekstual, kepemimpinan gereja yang relevan, serta keterlibatan kritis terhadap budaya digital. Pendekatan ini memungkinkan gereja tetap berakar pada iman Alkitabiah sekaligus relevan dan transformatif dalam kehidupan umat di tengah dinamika zaman.